History, landscape, and botanical report of a centenary square in Brazil - Marim Toledo, Jayca Amate; Vido Pereira, Barbara Cristina; Machado Mattiuz, Claudia Fabrino; Ambrosano, Marcelo Nalin; Casares, Maria Carolina; Trevisoli Silva, Angelo Gabriel; Ferraz, Marcos Vieira [UNESP] (Soc Brasileira Floricultura & Plantas Ornamentais, 2021)
Historical research of public spaces provides a better understanding of the social formation and preserve cultural and landscaping heritage. Jose Bonifacio Square, located in Picacicaba, Sao Paulo State, Brazil, is an important public space. We carried out a historical survey in the archives of municipal public institutions and a landscape record was done by identifying tree species implanted in the square. We verified a strong church influence in the development of the square landscape project. The first landscaping work occurred in 1885, and it became known as City Public Garden. It presented naturalistic features, using exotic and native species, mainly trees, for landscaping composition. Several modifications and reforms were made from 1885 to 2005. Jose Bonifacio Square was considered highly diverse (H' = 3.18) with 151 individuals, distributed in 36 species belonging to 14 botanical families. The native species from Atlantic Forest represented 82.6% of Bignoniaceae, Arecaceae, and Fabaceae species. The high diversity of native species found in Jose Bonifacio Square allowed us to infer a lower ecological fragility and a higher environmental balance than other Brazilian squares. The analysis of historical information from the years 1885 to 2019 and the analysis of the square's floristic composition in contemporary times demonstrated Jose Bonifacio Square's relevance in forming and conserving Piracicaba's urban
Keywords: historical garden; Jose Bonifacio Square; native trees; urban landscaping